BINA SEJAHTERA EMPLOYEE COOPERATIVE FINANCIAL INFORMATION SYSTEM BASED ON SAK-ETAP FOR MANAGERIAL DECISIONS - Heru Agus Triyanto; Danny Kriestanto; Sur Yanti (International Journal of Social Science, 2022)
The Bina Sejahtera employee cooperative or abbreviated as Kopkar Binatara STMIK AKAKOM has a savings and loan business unit and is also a shop division. The system was designed by creating context diagrams, level 0 DAD, relationships between tables and data dictionaries, input designs, and main menus and system views. Bina Sejahtera Employee Cooperative Financial Information System Based on SAK-ETAP Managerial Decisions only involve 2 (two) external entities, namely members and management of cooperatives. One of the outputs of this system will be the SHU report. Cooperative administrators provide data on cooperative management, position data, type of deposit data, savings transaction data, loan type data, loan transaction data, installment data, retrieval data, SHU data and obtain member reports, job reports, cooperative management reports, periodic savings reports, savings report per member, loan report per member, loan report per period, retrieval report per member, retrieval report per period, bad credit report per period, ceiling report per member, overall ceiling report, installment report per period, installment report per member, report on fines per period, interest report per period, SHU report per member, overall SHU report, Profit / Loss Report, Change in Capital Report, Balance Sheet Report from Bina Sejahtera Employee Cooperative Financial Information System Based on SAK-ETAP. The reports obtained from the system are complex but useful for managerial decisions